The Main Builders of Mediterranean Coralligenous: 2D and 3D Quantitative Approaches for its Identification - Bracchi, Valentina Alice; Bazzicalupo, Pietro; Fallati, Luca; Varzi, Andrea Giulia; Savini, Alessandra; Negri, Mauro Pietro; Rosso, Antonietta; Sanfilippo, Rossana; Guido, Adriano; Bertolino, Marco; Costa, Gabriele; De Ponti, Elena; et al. (Frontiers in Earth Science, 2022)
Along the Mediterranean Sea shelf, algal reefs made of crustose coralline algae and Peyssonneliales are known as coralligenous. It ranks among the most important ecosystems in the Mediterranean Sea, because of its extent, complexity and heterogeneity, supporting very high levels of biodiversity. Descriptive approaches for monitoring purposes are often aimed at assessing the surficial ephemeral canopy, which is sustained and controlled by the occurrence of the long lasting rigid structure at the base. This practice led to the non-univocal definition of coralligenous, sometimes indicated as “animal coralligenous” because of the surficial dominance of these components. The quantitative assessment of the builders that actively build-up the persistent structure through the geological time is therefore a fundamental topic. We collected two discrete coralligenous samples in front off Marzamemi village (Sicily, Ionian Sea), the first from an area of a dense coralligenous cover (- 37 m), and the second one from an area with sparse build-ups (- 36 m). By using image analysis and computerized axial tomography, we distinguished and quantified the different components both on the surface and inside the framework. In both cases, our results confirm the primary role of crustose coralline algae as major builders of the Mediterranean coralligenous, this aspect matching with the evidence from the Quaternary fossil record. We suggest that the role of encrusting calcareous red algae in the coralligenous should be considered in conservation and management policies.